1996
DOI: 10.1161/01.hyp.28.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Salt Intake and Plasma Atrial Natriuretic Peptide and Nitric Oxide in Hypertension

Abstract: In response to a high salt intake, salt-sensitive hypertensive individuals retain more sodium and manifest a rise in blood pressure greater than that in salt-resistant individuals. In this study, we tested whether salt sensitivity might be related at least in part to reduced secretion of atrial natriuretic peptide (ANP) or to abnormal nitric oxide production. We measured plasma ANP and NO2+NO3 in 7 normotensive individuals and 13 salt-sensitive and 14 salt-resistant blacks with essential hypertension under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
67
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 63 publications
2
67
1
1
Order By: Relevance
“…Thus, our observations in humans indicate that unlike the rat, total NO production measured from 24-hour U NOX V does not increase with increased sodium intake, at least over a 3-day period. In accordance with the present findings, Campese et al 30 reported that plasma NO X concentrations did not increase in healthy subjects given a high-salt diet. Conversely, Facchini et al 31 reported an inverse relationship between change in BP and change in U NOX V in healthy subjects in response to low versus high sodium intakes.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our observations in humans indicate that unlike the rat, total NO production measured from 24-hour U NOX V does not increase with increased sodium intake, at least over a 3-day period. In accordance with the present findings, Campese et al 30 reported that plasma NO X concentrations did not increase in healthy subjects given a high-salt diet. Conversely, Facchini et al 31 reported an inverse relationship between change in BP and change in U NOX V in healthy subjects in response to low versus high sodium intakes.…”
Section: Discussionsupporting
confidence: 93%
“…In the presence of hypertension and vasoconstriction, endogenous vasodilators such as members of the natriuretic family would be expected to be upregulated. Contrary to expectations, however, Blacks with hypertension induced by salt sensitivity have a reduction in one of the most potent of these vasodilators, A-type natriuretic peptide [36], compared to Whites with and without salt sensitivity and salt-resistant Blacks. This may represent a failure of microvascular protective measures against the effect of hypertension, resulting in the observed increase in minimal microvascular resistance.…”
Section: Discussioncontrasting
confidence: 70%
“…4 In animal models of salt-sensitive hypertension, the increase in BP after salt loading is characterized by reduced NO production. 8,13,14 Similarly, in humans with salt-sensitive hypertension, salt loading was associated with decreased plasma and urinary levels of NO metabolites. 3,13,14 A variety of evidence suggests that reactive oxygen species contribute to impaired endothelial function in several forms of hypertension and that there is increased oxidative stress in the microvessels of spontaneously hypertensive rats and Dahl salt-sensitive hypertensive rats.…”
mentioning
confidence: 99%
“…8,13,14 Similarly, in humans with salt-sensitive hypertension, salt loading was associated with decreased plasma and urinary levels of NO metabolites. 3,13,14 A variety of evidence suggests that reactive oxygen species contribute to impaired endothelial function in several forms of hypertension and that there is increased oxidative stress in the microvessels of spontaneously hypertensive rats and Dahl salt-sensitive hypertensive rats. [15][16][17] A recent report by Lenda et al 7 has suggested that reactive oxygen species can also contribute to a reduced endothelium-dependent dilation in normotensive rats on a high-salt diet.…”
mentioning
confidence: 99%